Prevención de Caídas: Soluciones para su hogar - Leigh Ann Martin; Emily A. Minton; Linda B Bobroff (EDIS)
Miles de adultos mayores se caen en su casa cada año. A medida en que uno envejece, su casa puede presentar algunos retos. Pero usted puede hacer cambios para que su casa cumpla con sus necesidades mientras reduce el riesgo de las caĺdas. This is the Spanish-language version of FCS2228/FY734, Fall Prevention: Solutions for Your Home. This 3-page document provides tips to help you reduce the risk of falls at home. Written by Leigh Ann Martin, Emily Minton, and Linda B. Bobroff, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised January 2018. http://edis.ifas.ufl.edu/fy858